Microstructure and microhardness alterations of inconel 718 under cryogenic cutting / Che Hassan Che Haron ... [et al.] - Che Haron, Che Hassan; Abdul Ghani, Jaharah; Faiq Azhar, Muammar; Abdul Halim, Nurul Hayati; Badroush, N. (Universiti Teknologi MARA, 2021)
This paper presents the experimental investigations to identify the effect of different machining parameters on the microstructure and microhardness alterations beneath the machined surface of Inconel 718. The high-speed milling experiments were conducted using PVD multi-coated ball nose carbide inserts, under cryogenic CO2 condition at controlled cutting speed of 120-140 m/min, feed rate of 0.15-0.25 mm/tooth, depth of cut of 0.3-0.7 mm and a fixed width of cut at 0.4 mm. The experimental results discovered that the formation of plastic deformation could only be observed when cutting with the highest value of feed rate and depth of cut, deepened until 8.87 µm from the machined surface. At the same time, those factors also significantly increased machined surface hardness, made the workpiece harder than its bulk hardness. However, the hardness values were found reduced towards the sub-surface and back to its bulk hardness approximately 250 - 300 µm from the top surface. This study suggests that the finishing milling process of Inconel 718 under cryogenic CO2 condition and at predetermined parameters can be performed at a depth of cut less than 0.3 mm as its machined sub-surface microhardness and microstructure alteration were observed to be inconsequential. Thus, a more economical machining process can be performed.